Expanding the Phenotypic and Genetic Spectrum of Neuromuscular Diseases Caused by DYNC1H1 Mutations - Li, Jia-Tong; Dong, Si-Qi; Zhu, Dong-Qing; Yang, Wen-Bo; Qian, Ting; Liu, Xiao-Ni; Chen, Xiang-Jun (Frontiers in Neurology, 2022)
Objectives Spinal muscular atrophy with lower extremity predominance 1 (SMALED1) and Charcot–Marie-Tooth diseasetype 2O (CMT2O) are two kinds of hereditary neuromuscular diseases caused by DYNC1H1 mutations. In this study, we reported two patients with SMALED1 caused by DYNC1H1 mutations. The genotype–phenotype correlations were further analyzed by systematically reviewing previous relevant publications. Materials and Methods Two patients' with SMALED1 and their parents' clinical data were collected, and detailed clinical examinations were performed. WES was then applied, which was confirmed by Sanger sequencing. PubMed, Web of Science, CNKI, and Wanfang Data were searched, and all publications that met the inclusion criteria were carefully screened. Any individual patient without a detailed description of clinical phenotypes was excluded. Results The two patients manifested delayed motor milestones and muscle wasting of both lower extremities. The diagnosis was further confirmed as SMALED1. Genetic testing revealed heterozygous DYNC1H1 mutations c.1792C>T and c.790C>G; the latter is a novel dominant mutation. Genotype–phenotype analysis of DYNC1H1 variants and neuromuscular diseases revealed that mutations in the DYN1 region of DYNC1H1 protein were associated with a more severe phenotype, more complicated symptoms, and more CNS involvement than the DHC_N1 region. Conclusion Our study potentially expanded the knowledge of the phenotypic and genetic spectrum of neuromuscular diseases caused by DYNC1H1 mutations. The genotype–phenotype correlation may reflect the pathogenesis underlying the dyneinopathy caused by DYNC1H1 mutations.